2020
DOI: 10.1038/s41598-020-77325-2
|View full text |Cite
|
Sign up to set email alerts
|

EpOMEs act as immune suppressors in a lepidopteran insect, Spodoptera exigua

Abstract: Epoxyoctadecamonoenoic acids (EpOMEs) are epoxide derivatives of linoleic acid (9,12-octadecadienoic acid) and include 9,10-EpOME and 12,13-EpOME. They are synthesized by cytochrome P450 monooxygenases (CYPs) and degraded by soluble epoxide hydrolase (sEH). Although EpOMEs are well known to play crucial roles in mediating various physiological processes in mammals, their role is not well understood in insects. This study chemically identified their presence in insect tissues: 941.8 pg/g of 9,10-EpOME and 2,198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Vatanparast et al [ 29 ] also introduced a new class of oxylipins in the biology of their model, S. exigua . These are oxygenated LA derivatives, epoxyoctadecamonoenoic acids (EpOMEs).…”
Section: Eicosanoid Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Vatanparast et al [ 29 ] also introduced a new class of oxylipins in the biology of their model, S. exigua . These are oxygenated LA derivatives, epoxyoctadecamonoenoic acids (EpOMEs).…”
Section: Eicosanoid Biosynthesismentioning
confidence: 99%
“…These are oxygenated LA derivatives, epoxyoctadecamonoenoic acids (EpOMEs). For background, Vatanparast et al [ 29 ] provided the chemical structures and outlined EpOME biosynthesis, beginning with release of LA from cellular PLs by a PLA 2 , an oxygenation step by a cytochrome P450 monooxygenase (CYP) and hydroxylation by an epoxide hydrolase. They determined the substantial presence of the compounds, nearly 1000 pg/g 9,10-EpOME and >2000 pg/g 12,13-EpOME in fat body.…”
Section: Eicosanoid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…We found that Sc-FARs bind to LA and oxidized metabolites of LA in vitro , which may suggest their preferred in vivo binding partners. Our metabolomics studies showed that arachidonic acid, 9(10)- and 12(13)-EpOME, and 13-HODE, which are known to modulate diverse physiological functions in mammals and have been shown to regulate immunity in insects (Vatanparast et al, 2020). 13-HODE has anti-inflammatory functions in mammalian immunity and is often increased under oxidative stress triggered during a disease response, are depleted in the hemolymph of FAR expressing flies (Thompson et al, 2005; Vangaveti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome p450 epoxygenases convert C18 unsaturated fatty acids, such as oleic acid, linoleic acid, and α-linolenic acid, into 9,10-epoxyoctadecanoic acid (Tsikas et al, 2003); 9,10-epoxy-12Z -octadecenoic acid (Spector and Kim, 2015) and 12,13-epoxy-9Z -octadecenoic acid (Vatanparast et al, 2020); 9,10-epoxy-12Z ,15Z -octadecadienoic acid (Wang et al, 2019), 12,13-epoxy-9Z ,15Z -octadecadienoic acid (Walker et al, 2021), and 15,16-epoxy-9Z ,12Z -octadecadienoic acid (Holt et al, 2015), respectively. Cytochrome p450 epoxygenases convert C20 and C22 PUFAs, such as arachidonic acid, eicosapentaenoic acid, and docosahexaenoic acid, into C20 and C22 EFAs, such as 5, 6-, 8,9-, 11,12-, and 14,15-epoxyeicosatrienoic acids, 5,6-, 8,9-, 11,12-, 14,15-, and 17,18-epoxyeicosatetraenoic acid, 7,8-, 10,11-, 13,14-, 16,17-, and 19,20epoxydocosapentaenoic acids, respectively (Spector and Kim, 2015).…”
Section: Introductionmentioning
confidence: 99%